2022
DOI: 10.29109/gujsc.1108504
|View full text |Cite
|
Sign up to set email alerts
|

Irrigatıon in Agriculture and Automation Based Irrigation Systems (Mini-Review)

Abstract: With the technological developments, modern agricultural applications and the effects of these applications in daily life are increasing day by day. Automation-based smart systems, which have replaced old-style fixed irrigation systems created for only a specific purpose, have brought along remote-controllable agricultural productions in line with agricultural product needs. Automation-based smart irrigation systems have brought significant gains to the agricultural sector. The most important of these gains ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The global population is expected to reach 9.61 billion by 2050 and 11.2 billion by 2100 (Nath et al, 2022). By 2025, it is predicted that this growth will be accompanied by a 60 % increase in the food requirements of the present population (Arık & Korkut, 2022). To fulfil the rising demand for food, agricultural productivity needs to be raised to preserve vitality (Aküzüm et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The global population is expected to reach 9.61 billion by 2050 and 11.2 billion by 2100 (Nath et al, 2022). By 2025, it is predicted that this growth will be accompanied by a 60 % increase in the food requirements of the present population (Arık & Korkut, 2022). To fulfil the rising demand for food, agricultural productivity needs to be raised to preserve vitality (Aküzüm et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of a rudimentary system that employs a microcontroller to automate the irrigation and watering of small potted plants or crops with minimal manual intervention is necessary. A system was developed that detects temperature and humidity changes in the environment using sensors and controls the pump via a signal sent by the microcontroller [20]. It was reported that the planned system was less expensive than other systems.…”
Section: Introductionmentioning
confidence: 99%